SPATIAL DISTRIBUTION OF CRIMINAL ACTIVITIES IN OWERRI, IMO STATE, NIGERIA - Chibo, Christian Nnamdi; Adol, Stacy Chimdia (African Journal of Social and Behavioural Sciences, 2020)
Crime can be seen to mean a list of specific forms of human conduct which has been outlawed by political and constituted authorities. The study centered on the spatial distribution of criminal activities in Owerri, Imo state, Nigeria. This it does with the specific aim of analyzing how crimes and criminal activities are spatially distributed within the three local government areas that constituted Owerri. The objectives of the study include among others; to investigate the categories of Criminal activities in Owerri in 2014 – 2015; examine the crime occurrence in the study area in 2014 – 2015; Produce the crime statistics map of the study area in 2014 – 2015 using Geographic Information System. Secondary data were generally used in the study. The major secondary data for this study was generated from Area Command, Owerri, Imo State. Data generated were presented and analyzed using frequency tables and percentages. Choropleth map was used to present the data produced on the crime statistic map of the study area. One hypothesis was tested at 95 percent (0.05) confidence interval. The hypothesis which seeks to investigate if there is a significant variation in the spatial distribution of criminal activities in Owerri was tested using One Way Analysis of Variance (ANOVA). The hypothesis shows that criminal activities in the study area were not spatially distributed. The result shows that armed robbery is the greatest criminal activities in Owerri north and Owerri west, while cult activities cuts across the three Local Government Areas, but was observed more in Owerri Municipal Council. The result also shows that the least criminal activities in Owerri are rape and murder. The study recommends among others that security should be beefed up in the area especially around the places with higher institutions, local and neighborhood securities should be formed to enhance securities, youths should be provided with employments, serious punishment should meted on those convicted of crimes, so as to serve as a deterrent to those wanting to go into crime, and higher institutions in Owerri should be more proactive against cult activities in their various institutions.